Drying effects on antioxidant activity, enzyme activity, and phytochemicals of avocado (Persea americana) leaves. Issue 10 (30th October 2018) - Loh, Zhi Hung; Lim, Yau Yan
Abstract : In this study, avocado leaves were dried by five different drying treatments: oven‐drying at 50 and 100 °C, microwave‐drying, ambient air‐drying, and freeze‐drying. Investigation showed that oven‐drying and ambient air‐drying of leaves caused decrease in antioxidant properties while microwave‐drying and freeze‐drying preserved them. Polyphenol oxidase (PPO) and peroxidase (POD) activities decreased notably after drying in oven at 50 and 100°C, microwave, ambient air and blanching at 100°C. However, increase in PPO was observed in freeze‐dried leaves. Chlorogenic acid and rutin present in leaves showed varying decrease in drying processes except microwave‐drying, and freeze‐drying. Cellular antioxidant assay revealed reduced antioxidant activity in all drying treatments except for microwave‐drying. Factors that affected changes in antioxidant properties by various drying processes were identified and discussed. Microwave‐drying was considered to be the best drying method for avocado leaves as phenolic compounds were preserved and PPO and POD activities were deactivated. Practical applications: Avocado leaves are used as herbal tea in traditional medicine and are reported to have medicinal properties such as antioxidant, anti‐viral, and anti‐inflammatory. Processing of fresh herbal tea leaves are required to preserve phenolic compounds and quality of the tea leaves. This study represents a comprehensive study on the effects of different drying treatments on the antioxidant activity using both in vitro and in vivo analysis and enzymatic changes of avocado leaves. The optimum drying condition found in this study will be beneficial to the tea processing industry.